The Diversity Of Worldviews Among Young Adults
XXV, 381 p. 33 illus.
Keywords: This open access volume features a data-rich portrait of what young adults think about the world. It collects the views of students in higher education from various cultural regions, religious traditions, linguistic groups, and political systems. This will help readers better understand a generation that will soon rise to power and influence. The analysis focuses on 12 countries. These include Canada, China, Finland, Ghana, India, Israel, Peru, Poland, Russia, Sweden, Turkey, and the USA. It employs a mixed-methods approach, invested in the study of an individual's views and values using state-of-the-art methodology, including the innovative Faith Q-sort. This instrument is new to the field and developed for assessing the entanglement of subjective views and personal beliefs. The study also incorporates a comprehensive values survey as well as other survey tools that look into people's social capital, media use, social values alignment, and subjective well-being. Each chapter is co-authored by an international team of scholars with research interest in the particular topic. The rationale for this principle is the need to engage individuals from different cultural backgrounds, scholarly disciplines, and methodological and substantive competences. In the end, this innovative approach presents an informed, empirically grounded analysis of the values and worldviews of the future generation. It sheds an important light on how changes in the religious landscape are intertwined with broad and diffuse processes of socio-economic and global cultural change.